Rare clinical manifestation of community-acquired pneumonia. Issue 1 (28th November 2018) - Brikman, Shay; Levi, Omri; Dori, Guy
Abstract : A 71-year-old patient was admitted due to fever and persistent (>48 hours) hiccups. History and physical examination were not instructive. Lab tests were not specific, showing an inflammatory response. Chest film did not demonstrate opacities. The patient was treated with chlorpromazine with no relief. Fever and hiccups persisted, and therefore neck and chest CT was performed revealing a right lower lobe infiltrate, a finding consistent with pneumonia. Antibiotics were initiated and within 48 hours fever and hiccups resolved and patient recovered. Although hiccups are rarely described as a clinical manifestation of community acquired pneumonia, one should consider this diagnosis in a patient with unexplained fever.